SEMINARIUM NAUKOWE „TERRORYZM A PRAWA CZŁOWIEKA” NA WYDZIALE PRAWA I ADMINISTRACJI UNIWERSYTETU RZESZOWSKIEGO - Pastuszko, Grzegorz (My University, 2015)
The presented report describes the seminar that took place on 1st of December in the building of the Law and Administration Faculty of University of Rzeszów. The seminary was devoted to the problem of terrorism in the context of human rights. The organizers invited three notable guests: gen. bryg. rez. dr inż. Tomasz Bąk, mjr Adam Bogacz, doc. dr Krzysztof Czubocha, who made very interesting speeches, including practical and theoretical issues. The event gathered many listeners, especially students, but also workers of the University.
RESEARCH SEMINAR „TERRORISM A HUMAN RIGHTS” OF THE LAW AND ADMINISTRATION FACULTY OF UNIVERSITY OF RZESZÓW
1 grudnia 2014 r. w budynku Wydziału Prawa i Administracji Uniwersytetu Rzeszowskiego odbyło się seminarium naukowe poświęcone problematyce zagrożeń, jakie dla praw jednostki niesie w dzisiejszym świecie zjawisko terroryzmu. Seminarium zorganizowali pracownicy Katedry Instytucji Prawnych i Praw Człowieka działającej pod kierownictwem prof. zw. dr hab. H. Zięby-Załuckiej. Inicjatywa ta spotkała się z dużym zainteresowaniem ze strony studentów, a także pracowników Wydziału Prawa i Administracji.
Keywords: seminarium, terroryzm, prawa człowieka